trnS_trnG_Alignment_58seq - Eidesen, Pernille Bronken; Alsos, Inger Greve; Brochmann, Christian (Dryad Digital Repository, 2015)
Alignment file for trnS-trnG region based on plastid sequences used to generate haplotypes